An Optically Controlled Virtual Microsensor for Biomarker Detection In Vivo. Issue 47 (3rd October 2022) - Zhang, Tiange; Wu, Shuai; Qin, Haifeng; Wu, Huaying; Liu, Xiaoshuai; Li, Baojun; Zheng, Xianchuang
Abstract: Current technologies for the real‐time analysis of biomarkers in vivo, such as needle‐type microelectrodes and molecular imaging methods based on exogenous contrast agents, are still facing great challenges in either invasive detection or lack of active control of the imaging probes. In this study, by combining the design concepts of needle‐type microelectrodes and the fluorescence imaging method, a new technique is developed for detecting biomarkers in vivo, named as "optically controlled virtual microsensor" (OCViM). OCViM is established by the organic integration of a specially shaped laser beam and fluorescent nanoprobe, which serve as the virtual handle and sensor tip, respectively. The laser beam can trap and manipulate the nanoprobe in a programmable manner, and meanwhile excite it to generate fluorescence emission for biosensing. On this basis, fully active control of the nanoprobe is achieved noninvasively in vivo, and multipoint detection can be realized at sub‐micrometer resolution by shifting a nanoprobe among multiple positions. By using OCViM, the overexpression and heterogenous distribution of biomarkers in the thrombus is studied in living zebrafish, which is further utilized for the evaluation of antithrombotic drugs. OCViM may provide a powerful tool for the mechanism study of thrombus progression and the evaluation of antithrombotic drugs. Abstract : A new technique for biomarker detection in vivo, named as "optically controlled virtual microsensor" (OCViM), is developed by employing a specially shaped laser beam as a virtual handle and a fluorescent nanoprobe as the sensor tip. With the advantages of noninvasiveness, active control, and high resolution, OCViM demonstrates great potential for studying thrombosis in living zebrafish.